Uso da tetraciclina na neutralização das ações enzimáticas causadores de hemorragia, necrose e inflamação induzidos pela peçonha de Bothropoides erythromelas - Santos, João Victor de Almeida (2013)
Snake envenoming is a common medical emergency in the countryside of tropical countries. In Brazil, botropic snakes are the major responsible for the ophidian accidents related in that country. In Northeastern Brazil, Bothropoidess erythromelas, popularly known as “jararaca-da-seca”, can be found. Botropic venoms cause tissue damage at the bitesite, such as pain, edema, hemorrhage and necrosis. Traditional serum therapy has no efficacy against these effects, which stimulate the research for neutralizer agents. Several studies showed the neutralizing action of tetracyclines against snake venom local tissue effects. This work aimed to evaluate the effect of tetracycline, when preincubated, against in vitro proteolytic and phospholipase A2 activities, and hemorrhagic, necrotic and inflammatory actions in mice skin induced by B. erythromelas venom, besides investigating gene transcription of the inflammatory mediators involved. Results showed that proteolytic activity (101,2 ± 2,56%) was reduced to 6,59 ± 0,92%. Phospholipase A2 activity was reduced from 0,04 ± 0,001 to 0,02 ± 0,003, in absorbance values. The halo area of hemorrhagic (117,3 ± 7,005 mm2) and necrotic (20,79 ± 0,003 mm2) activities was totally abolished when tetracycline concentration was 10-fold the venom concentration. The neutrophil migration kinetics presented two peaks in 2h (19,977 ± 3,054 neutrophils/mg) and 72h times (115,265 ± 20,106 neutrophils/mg). These values were reduced by tetracycline treatment to 2.020 ± 210,2 neutrophils/mg and 16,506 ± 5.412 neutrophils/mg, respectively. Investigation of the inflammatory mediators involved showed increase in gene transcription levels IL-1β and IL-6 cytokines 30 minutes after envenomation. It was suggested that these effects are due, in part, to the chelation property of tetracycline on venom metalloproteinases enzymes, which are involved in the local tissue effects observed. In conclusion, tetracycline prevents proteolytic, phospholipase A2, hemorrhagic and necrotic activities, and neutrophil migration induced by B. erythromelas venom.